The salience of sport in cross-race friendship selection - Jones, Gareth; Bunds, Kyle S.; Carlton, Troy A.; Edwards, Michael B.; Bocarro, Jason N. (Journal of Amateur Sport, 2016)
In response to growing racial concerns, stakeholders have called for programs that facilitate positive cross-race interactions. Adolescence has been targeted as the most effective life stage to initiate programs promoting relationships. Since schools are one of the primary social influences on adolescent development, they have been emphasized as a particularly important setting for promoting intergroup contact. Sport plays an important role in the experiences of students, and contributes to intergroup relations within a school. The purpose of this study is to examine the unique effect of sport participation on cross-race friendship selection. Using data from Wave I of The National Longitudinal Study of Adolescent Health (Add Health), mixed-effects regression models and analysis of variance (ANOVA) were used to assess the effects of sport participation on friendship heterogeneity. Overall, participation in sport activities did not significantly influence the racial heterogeneity of adolescent’s friendship networks.